Application of lean management in the optimization of thyroid puncture appointment process - LI Guang-han, LI Ying, GUO Ke-ke, GAO Peng, ZHANG Wei-shuo, TU Ling, ZHANG Bo (Jichu yixue yu linchuang, 2020)
Objective To optimize the appointment process of thyroid fine needle aspiration by using the theory of lean management. Methods From June to September 2019, the patients who had thyroid puncture appointment in the ultrasound department of China-Japan friendship hospital were studied.Fifty patients before and after the process improvement were randomly included in the control group and 50 patients after the process improvement were in the study group. A total of 100 patients were collected. The total time of the appointment process, the total walking distance and the number of round trips of the appointment process, and the patient satisfaction were compared between the two groups. Results After the improvement, the time of appointment process was reduced from (58.6±31.5)min to (32.5±12.8)min; the satisfaction score of patients was increased from 3.3 to 4.3; and the walking distance was reduced from (90~546)m to (94~219)m, among which the walking distance involving the application form and payment of ultrasound examination was reduced from 78-149 m to 7 m, the total number of waiting in queues reduced from 3-7 to 1-2. Conclusions Based on the optimization method of lean management, it can optimize the process of patients' appointment and improve patients' satisfaction, which is conducive to the more efficient operation of the hospital's overall resources.